Perspectives of patients with advanced or metastatic non-small cell lung cancer on symptoms, impacts on daily activities, and thresholds for meaningful change: a qualitative research study - Cardellino, Anna; Shah, Manasee; Hanlon, Jennifer; Kelly, Kimberly; Martin, Alexandra; Roborel de Climens, Aude; Taiyari, Sara; Stojadinovic, Alexander (Frontiers in Psychology, 2023)
Introduction Advanced or metastatic non-small cell lung cancer (NSCLC) is associated with significant symptom burden. It is important to understand the impact of these disease-and treatment-related symptoms on patients’ daily lives and explore from a patient perspective what constitutes a meaningful change in NSCLC symptoms. Methods Patient experience of advanced or metastatic NSCLC was explored in this prospective, non-interventional qualitative research study recruiting patients from the United States (US). Interviews were conducted to explore the most important symptoms, daily life impacts, and patients’ perspectives of what constitutes meaningful change when considering their current symptoms versus 6–12 months prior, based on the Patient Global Impression of Severity (PGI-S) and Patient Global Impression of Change (PGI-C) items. Results Between February and April 2022, 19 US-based patients with Stage IV NSCLC were recruited; 95% were female, 63% were White, 79% had been diagnosed >1 year prior, and 63% were receiving targeted therapy. Over half the patients indicated their most important symptoms were fatigue, shortness of breath, and cough. Patient differentiation between whether symptoms were disease- or treatment-related lacked concordance, and often patients were unable to distinguish the two. The most frequently mentioned impacts of these symptoms on patients’ daily lives were difficulty walking, sleep disturbance, anxiety/depression, impact on relationships, and difficulty doing daily tasks. Most patients considered a one-point change on the PGI-S or PGI-C to be meaningful based on rating their symptom severity at the time of the interview compared with 6–12 months before the interview. Conclusion Based on their own symptom experience, patients with advanced or metastatic NSCLC indicated a one-point threshold for meaningful change, whether improvement or worsening. This suggests a one-point change on the PGI-S or PGI-C may be a potential anchor for patient-reported outcome (PRO) endpoints used in clinical trials. It is important to use PRO instruments that capture the symptoms and impacts identified as most important to patients. These findings highlight the importance of using qualitative methods to assess disease-related symptoms, treatment-related side effects, and the impacts on daily life for patients with advanced or metastatic NSCLC, underscoring how qualitative assessments can complement quantitative PRO instruments for evaluating clinical trials.